2012
DOI: 10.3390/rel3020467
|View full text |Cite
|
Sign up to set email alerts
|

Religious and Spiritual Biomarkers in Both Health and Disease

Abstract: Religious thought and spirituality can be considered as a part of natural human capacities. There is an exponential rise in clinical research in the relationship between religion, spirituality and positive health outcomes. Most of these studies, however, have been primarily descriptive, rather than explanatory, focusing on identifying their underlying mechanisms. Almost no attempts have been made to find novel methods to mirror and monitor positive, and possibly negative, reactions related to the local and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 152 publications
(192 reference statements)
0
12
1
3
Order By: Relevance
“…Previous reports have shown that the diet may affect the levels of ethanol [36,37]. In our study there was a tendency for higher levels of breath ethanol 30 minutes after the ingestion of food however this was not statistically significant.…”
Section: Discussioncontrasting
confidence: 78%
“…Previous reports have shown that the diet may affect the levels of ethanol [36,37]. In our study there was a tendency for higher levels of breath ethanol 30 minutes after the ingestion of food however this was not statistically significant.…”
Section: Discussioncontrasting
confidence: 78%
“…Studies demonstrated the positive impact of spirituality on physical health and mental health as well as on other positive health outcomes such as subjective well-being, health-related quality of life, coping skills, recovering from mental illness, or less addictive or suicidal behaviors (Mueller et al, 2001;Miller and Thoresen, 2003;Kharitonov, 2012;Unterrainer et al, 2014). However, we must bear in mind that spirituality is a complex construct and as such it is defined in multiple ways and measured with different tools (Lun and Bond, 2013).…”
Section: Spiritualitymentioning
confidence: 99%
“…Moreover, in most Christian religions (which is the predominant religion among AA women [ 13 ]), there is shared belief in a supernatural creator (i.e., God) that informs these formal practices and beliefs [ 12 ]. We defined spiritually as a more general, unstructured, personalized, and naturally occurring phenomenon where a person seeks closeness and/or connectedness between him/herself and a higher power or purpose [ 12 , 14 , 15 ]. Based on these definitions, both religion and spirituality focus on increasing connectedness with a higher power, but each has a different approach.…”
Section: Introductionmentioning
confidence: 99%